Philosophical Basis of the Compulsory Company Manpower Report toward Pancasila Industrial Relation - Sarira, Iron (Humaniora, 2019)
The research aimed to find out the intrinsic meaning and pragmatic interests of the concept of Compulsory Company Manpower Report (CCMR) and how the principle basis of Law Number 7 Year 1981 affected philosophical validity in realizing industrial relation in accordance with Pancasila. The research applied a qualitative method with textual analysis. The media of research was CCMR, which was one of the minimum macro aspects (work norm) in labor inspection as regulated in Law Number 7 Year 1981 aiming to implement the policy of work opportunity expansion and work protection as mandated by Article 27 paragraph (1) of the 1945 Constitution. The results report the conditions of employment within a company having historical and meaningful substances as the 1945 Constitution states the existence of equality in law and government for every citizen, and each citizen shall uphold the law and government as a manifestation of an active role of citizenship. The applicability of a positive norm cannot be separated from its juridical, sociological, and philosophical requirements. Many opinions reveal that CCMR is only for operational administrative fulfillment. Meanwhile, there is a philosophical basis of CCMR that reaches to the idea about conceptions in work opportunity and labor protection to realize harmonious, dynamic, and fair industrial relations in accordance with Pancasila.